1984
DOI: 10.1007/bf00328195
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy of sacrospinal muscle groups in patients with chronic, diffusely radiating lumbar back pain

Abstract: After surgery necessitated by lumbar back pain syndromes, radiolucency verified by CT may appear in the sacrospinal muscle group on the operated side. This radiolucency represents muscular atrophy and is in its most severe form a result of the replacement of muscle tissue with adipose tissue. Such muscular atrophy appeared in the present series in 31 out of all 156 patients (19.9%) and in 29 out of 94 patients operated on because of radiating lumbar back pain (30.9%). The radiological appearance, extent, and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 18 publications
2
31
0
4
Order By: Relevance
“…Again these changes were localized to the level of injury and were associated with rapid changes in intra-muscular fat. Several studies evaluated the association between CT-evaluated paraspinal muscles density and LBP [14,15,19,28,29,34,40]. Muscle density is an expression of degeneration of the muscles and reflects the number of muscle fibers, the area of the individual muscle fiber, and the packing of the contractile material [22], whereas the CSA is mainly determined by the total number of muscle fibers, to a lesser degree, the size of the fibers [35,36], and the quantity of fat in the muscle [6,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again these changes were localized to the level of injury and were associated with rapid changes in intra-muscular fat. Several studies evaluated the association between CT-evaluated paraspinal muscles density and LBP [14,15,19,28,29,34,40]. Muscle density is an expression of degeneration of the muscles and reflects the number of muscle fibers, the area of the individual muscle fiber, and the packing of the contractile material [22], whereas the CSA is mainly determined by the total number of muscle fibers, to a lesser degree, the size of the fibers [35,36], and the quantity of fat in the muscle [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…Muscle density is an expression of degeneration of the muscles and reflects the number of muscle fibers, the area of the individual muscle fiber, and the packing of the contractile material [22], whereas the CSA is mainly determined by the total number of muscle fibers, to a lesser degree, the size of the fibers [35,36], and the quantity of fat in the muscle [6,9]. Laasonen [34] more than two decades ago described the decrease in CT-evaluated density of sacrospinal muscles after spinal surgery. In a study of Hultman et al [19], CT-evaluated density of erector spinae was significantly decreased in males with chronic (more than 3 years) LBP compared to males without chronic LBP.…”
Section: Discussionmentioning
confidence: 99%
“…38 Reduced muscle CSA was seen using RUSI in patients prior to surgery with atrophy being more severe in those with greater LBP. 32 Postoperative images showed no further decrease in CSA.…”
Section: Prelumbar Surgery and Postlumbar Surgerymentioning
confidence: 93%
“…32,38,66 In cases of unilateral LBP, researchers using computed tomography found that paraspinal muscles were 10% to 30% smaller on the affected side com-…”
Section: Prelumbar Surgery and Postlumbar Surgerymentioning
confidence: 99%
“…31,49,70,77,105,120 In particular, they provide useful qualitative/quantitative measures concerning the muscular system, including the consequential muscular degeneration (atrophy and fatty infiltrate) shown to be common in patients with low back pain, 11,22,47,51,66,75,84,95 neck pain, 1,30,40,74,83 and other peripheral musculoskeletal disorders. 124 Although MRI is considered the gold standard for musculoskeletal imaging, emerging applications of USI and CT are capable of providing insight into in vivo features of the musculoskeletal system.…”
Section: M-mode Ultrasound Imagingmentioning
confidence: 99%